Algorithms of resistance: the everyday fight against platform power - Bonini, Tiziano; Treré, Emiliano (Cambridge, Massachusetts: The MIT Press, 2024)
"Bonini and Trere explore how people all around the world use different tactics to interfere with the algorithms behind the platforms they use to work, entertain, and inform themselves"-- Living with algorithms : power, agency, resistance -- The moral economy of algorithmic agency -- "Gaming" the boss -- "Gaming" culture -- "Gaming" politics -- Frontiers of resistance in the automated society. "Bonini and Trere explore how people all around the world use different tactics to interfere with the algorithms behind the platforms they use to work, entertain, and inform themselves"--